Parity influences postpartum adaptations in the maternal gut microbiota - Zharkyn Jarmukhanov; Elizaveta Vinogradova; Nurislam Mukhanbetzhanov; Samat Kozhakhmetov; Deniza Khassenbekova; Almagul Kushugulova (Scientific Reports)
Abstract The gut microbiome undergoes substantial modifications during pregnancy, yet its postpartum adaptations remain poorly understood, particularly with respect to the influence of parity. Here, we investigated the impact of childbirth history on maternal gut microbiome composition and function one month postpartum. By conducting metagenomic sequencing analysis on 60 participants (34 postpartum mothers and 26 controls), we demonstrated significant differences in microbial diversity and community structure between postpartum mothers and control, as well as subtle differences between first-time mothers and multiple-birth mothers. We identified parity-specific signatures, with first-time mothers showing enrichment in Dysosmobacter welbionis, Candidatus Saccharibacteria, and Anaerotruncus species. Functional analysis revealed distinct metabolic reprogramming patterns, including increased amino acid biosynthesis and modified fermentation pathways supporting postpartum recovery. We observed significant correlations between specific bacterial taxa and metabolic pathways, particularly in energy metabolism and immune modulation. Notably, the enhanced capacity for short-chain fatty acid production in primiparous mothers, mediated by Anaerotruncus and Dysosmobacter welbionis, suggests a potential role in shaping breast milk composition, which may influence neonatal development. These findings establish the concept of parity-dependent microbiome programming and provide insights into the biological mechanisms underlying maternal adaptation to pregnancy and childbirth.